IMPACT OF HYGIENE AND SANITATION ON REVISIT INTENTION AT SANTIKA DEPOK HOTEL - ., Sofiani (Journal of Business And Entrepreneurship, 2020)
Achieving universal access to adequate sanitation and improved hygiene is an essential step on every country’s journey to securing good health for its citizens. The good hygienic practices are mandatory standards for all industries, including the hotel industry. To be able to stay competitive in the industry, it is crucial for hotel operators to consistently improve their internal factors, e.g. hygiene and sanitation, towards achieving successful occupancy rate. The objectives of this study are to investigate the effects of the hygiene and sanitation on the intention to revisit Santika Depok hotel and to suggest recommendation on ways to improve the hotel occupancy rate. The overall finding of this study suggests that hygienic room attendant influences hotel guests to revisit, meanwhile the sanitation of the room and hotel environment do not.